A cobra e os poetas: uma mirada selvagem na literatura brasileira - Mario Geraldo Rocha da Fonseca (2013)
Cobra (Snake) is the main term of this research. This is why it starts by proposing that the term refers to a concept, a map and a character, in order to defend the idea that, in Brazilian literature, there is a lineage of writers who practice what this thesis calls ophidian writing. The three mentioned levels (concept, map, character) are articulated by the Cobras own ways, which receives here the name of deviation. In this way, the thesis starts by defining what is this deviation, articulating it with some contemporary concepts of literary theory. In the first chapters, it seeks to establish the places of this deviation. The first deviation, therefore, is where was placed the notion of the literary representation of the indigenous, still very much used in the studies of a certain lineage of Brazilian writers who took to the Indian type as a fundamental reference to construct their literature. In this way, it proposes another way of working with the commonly called literary representation of the indigenous and with the related debates that issued from the Semana da Arte Moderna, in 1922. In this way, it proposes another cartography for the historicunderstanding of the commonly called writers of the indigenous. Thus it uses the term Cobra to articulate a new place that can be articulated not by the referred concept of literary representation of the indigenous, but by the look that is emerging from what is being called Indian literature, through the books that are arriving from the Indian settlements. From the compiled, studied and disseminated myths of the books produced bythe Indians themselves, or by themselves with anthropology and literature researchers, particularly the Kaxinawa Indians (State of Acre) and the Sateré-mawé (State of Amazon), the Cobra assumes the condition of a character that will travel (map, history), analyze (theory, method) and enter in dialogue with the canon of the literary representation of the indigenous and with its contemporary inventions. This look of the Cobra also receives the name of wild reading, because it refers to a vision that attempts to assume the perspective of the perspectivismo ameríndio as it is proposed by the researchers inanthropology who took to the openings of the wild philosophy of Nietzsche, Deleuze, Derrida, Agamben, as well as Freud and Benjamin, among others.